Bilateral Non Arteritic Anterior Ischemic Optic Neuropathy Associated With Optic Nerve Head Drusen And Vascular Risk Factors - Eathi Tuli; Aakanksha Sharma; Gaurav Sharma; Shalu Gupta (Delhi Journal of Ophthalmology)
We report case history of 52 year old male who presented with sudden painless diminution of vision in right eye and with similar complaint of diminution of vision in left eye six months back. He was diagnosed as Nonarteritic Anterior Ischemic Optic Neuropathy (NAION) in left eye with Optic Nerve Head Drusen (ONHD) in both the eyes. He was otherwise well and his medical history revealed systemic hypertension. Fundus examination revealed hyperaemic disc in the right eye and temporal pallor of the disc in the left eye. On visual field examination, inferior altitudinal visual field defect in both the eyes. ONHD can mimic as disc oedema and it can very rarely cause NAION. In addition, multiple vascular risk factors can also cause NAION, hence detailed investigations and periodic follow up should be done to rule out ischemic disc complication.